Religious-Friendly Tourism: Solutions For Increasing And Developing Indonesian Tourism - Irawan, Bambang; Hartono, Hartono; Sudinta, Heru (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine (1) the potential of religious friendly tourism to increase and develop Indonesian tourism; and (2) strategies to increase and develop Indonesian tourism through religious friendly tourism. The data analysis technique used in this research is SWOT analysis. The results of this research show (1) religious friendly tourism has the potential to increase and develop Indonesian tourism with the diversity of national tourism resources, the public's attention and positive attitude towards the development of halal tourism, as well as Indonesia's position as a destination country for halal tourism investment as a country with a Muslim majority. and (2) Indonesian tourism development strategy based on SWOT analysis consisting of SO strategy through marketing religious-friendly tourism to increase and develop Indonesian tourism, WO strategy through offering religious-friendly tourism concepts for tourists, ST strategy through collaboration with stakeholders to support religious-friendly tourism, and WT strategies through education on the concept of religious-friendly tourism.